Role of post-transplant graft scintigraphy in kidney donation after circulatory death - Belhoste, Manon; Allenbach, Gilles; Agius, Thomas; Meier, Raphael P. H.; Venetz, Jean-Pierre; Corpataux, Jean-Marc; Schneider, Antoine; Golshayan, Déla; Prior, John O.; Déglise, Sébastien; Nicod-Lalonde, Marie; Longchamp, Alban (Frontiers in Transplantation, 2022)
Background There is no consensus on how to predict post-transplant function of donation after circulatory death (DCD) kidneys. Thus, we aimed to identify renal scintigraphy parameters that could predict 1-year kidney function. Methods In this single center study, we included all consecutive DCD kidney recipients between 2013 and 2021 (n = 29). Patients who did not have a scintigraphy within 10 days of transplantation (n = 3), recipients of multiple organs and less than 18 years old were excluded (n = 1). Primary endpoint was the estimated glomerular filtration rate (eGFR). Results Median eGFR and serum creatinine at 1 year were 67 µmol/L (56–81) and 111 ml/min (99–132), respectively. Among parameters tested, the 3rd/2nd-minute activity ratio had the best diagnostic performance (AUC: 0.74 and 0.71, for eGFR and creatinine) 1 year post transplantation. Using 1.21 as the best cut off, the 3rd/2nd-minute activity ratio specificity and sensitivity to predict eGFR >60 ml/min was 0.82 and 0.83. Renal function was significantly better at 1 week, 3, 6, and 12 months after transplantation in patients with 3rd/2nd-minute activity ratios above 1.21. Conclusion This study suggests that the 3rd/2nd-minute activity ratio can predict graft function at 1 year. The benefit of post-transplant scintigraphy should be further validated in a prospective cohort.